Perilaku Manusia Dalam Perspektif Psikologi Sosial - Hasan Mustafa (Jurnal Administrasi Bisnis, 2011)
Although social psychology is the discipline that has long existed (since Plato andAristotle), but officially, the discipline has become a new independent science in1908. Brief article below attempts to explain human behavior from different points ofview or perspective that is generally studied in social psychology. The perspectivesthat discussed in this article are the behavioral perspectives, cognitive perspectives,structural perspectives and interactionist perspectives. Through the study of variousviewpoints we were able to understand human behavior in a more comprehensive.Keywords: Organizational behaviour, human resources management, consumerbehaviour